Comparison of the Frontal Plane Projection Angle and the Dynamic Valgus Index to Identify Movement Dysfunction in Females with Patellofemoral Pain - Lori A Bolgla; Haley N Gibson; Daniel C Hannah; Tiana Curry-McCoy (International Journal of Sports Physical Therapy)
# Background